The Last of England: A Work for Solo Piano After the Painting by Ford Madox Brown - Chew, Richard (Australasian Journal of Victorian Studies, 2020)
This paper considers the creative process of writing music in response to a visual work of art. My piano composition The Last of England (2016) is named after the famous painting by Ford Madox Brown (1852-55). It is a work in 15 movements, a narrative composition in which I invite the listener to embark on a journey into the world of the painting and the scene it represents. In the nineteenth century, music which sought to represent the natural world, to convey an extra-musical narrative, or that which was inspired by literary or artistic source works, was classified broadly as program music. Siglind Bruhn argues however, that certain pieces of music go much further, and aspire to an ‘interartistic mode of transfer’, a musical equivalent of literary ekphrasis, in which the form, structure and metaphoric content of the source work is ‘transposed’ from one medium to another (2001). The composer ‘performs’ the painting. Having considered some prominent examples of literary and musical ekphrasis, I proceed to a discussion of the making of this composition: its musical characteristics, influences, and the ways in which it seeks to re-present Madox Brown’s vision.